(untitled) (Research, Society and Development, 2022)
This work explores the collection of publications of the National Association of Graduate Studies in Administration (ANPAD), specifically in the events National Meeting of Organizational Studies (EnEO) and Meeting of People Management and Labor Relations (EnGPR), identifying the articles that deal with gender issues and race relations in the organizational context. Aiming to analyze the main characteristics of publications on these topics, the methodology used qualifies the research as bibliographic and descriptive using VOSviewer. The results found indicate that the articles present a strong prevalence of works on gender, addressing issues related to inequality and describing the difficulties experienced by women when performing roles historically destined for men, such as leadership and entrepreneurial practice. The analysis of keywords and research objectives converges with this reading. The distribution of publications over time identifies a fragmentary aspect, not suggesting a strengthening of research in the field. As for the methodological aspects, the publications follow trends in the field of research in the field of organizational studies, presenting a large majority of qualitative studies, using interviews and/or case studies as a data collection technique and highlighting content analysis. in the discussion of the results.